Hubungan Diversitas Makanan Terhadap Pertumbuhan Anak Usia Baduta (6–24 Bulan) - Shentya Fitriana; Rahmatul Ulya (Nan Tongga Health And Nursing, 2026)
Child growth during the first two years of life is a critical period that determines health status and human resource quality in the future. One important factor influencing child growth is the diversity of food consumed, especially during the complementary feeding period. Adequate dietary diversity ensures the fulfillment of essential macro and micronutrients needed for optimal growth and development. This study aims to analyze the relationship between dietary diversity and the growth of children aged 6–24 months in the working area of Puskesmas Nanggalo, Padang. This research used a quantitative approach with an analytic observational design using a cross-sectional method. The sample consisted of 60 children aged 6–24 months selected using purposive sampling techniques. Data on dietary diversity were collected through structured interviews with mothers using a 24-hour recall questionnaire and measured using the Minimum Dietary Diversity (MDD) indicator. Child growth data were obtained through anthropometric measurements including weight and length/height according to age standards. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. The results showed that there was a significant relationship between dietary diversity and child growth with a p-value of 0.012 (p < 0.05). Children who had good dietary diversity tended to have better growth compared to children with low dietary diversity. These findings highlight the importance of improving dietary diversity during the complementary feeding period to support optimal child growth.